The role of air transport in developing tourism activity in Sulaymaniyah Governorate for the period (2005 - 2018) "An analytical study" - Ranj Tahir Abdullah,; Bazar Nasruddin Majid,; Younis Ali Ahmad, (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Transport facility is considered one of the main reasons for the progress of tourism and its development. Today, air transportation is one of the most important means to promote tourism activity. Therefore, it is one of the basic elements affecting the tourist destination and arriving in the least time and effort. The importance of this study comes from the role of air transportation in promoting the tourism activity in the province of Sulaymaniyah. The main objective of the study is to analyze the economic role of Sulaymaniyah International Airport in promoting tourism activity in Sulaymaniyah Governorate, identifying and diagnosing the problems and obstacles facing air transportation, as well as presenting proposals for airport development. In order to achieve the study objectives, official data for the period of (2005-2018) has been obtained and analyzed. One of the most important findings of the study is that despite the instability in the economic and political conditions in recent years in the Kurdistan Region in general and in the Governorate of Sulaymaniyah in particular, in addition to the closure of the airport of Sulaymaniyah for a little bit long term and the suspension of the work of some airline companies, and the blockade by the neighboring countries on the Sulaymaniyah airport, there are a positive indicators of the activity of the Sulaymaniyah International Airport, especially in the field of the movement of tourists and internal and external flights.